Cross-leveraging synergistic benefits from across an event portfolio: Empirical evidence from Madeira - Brian Garrod (Journal of Destination Marketing & Management, 2021)
While most tourism destinations host a range of events, these are often planned and delivered without explicit reference to one another. There may, however, be benefits to recognising the potential inter-relatedness of events in a destination and developing synergies between them. This study analyses a calendar of events based in Madeira, Portugal, to identify areas of relatedness that could be cross-leveraged by managing and marketing the events as a strategic portfolio. Accordingly, a questionnaire was administered among attendees at five major events, yielding 3118 responses. These data were analysed using ANOVA and two types of regression. The results suggest that, firstly, it is prudent to employ a range of analytical techniques to the available data to identify appropriate strategic levers. Secondly, the findings demonstrate the potential for post-hoc analysis not only to identify areas of relatedness between the events but also to discover gaps that can be filled by new events. Thirdly, the findings emphasise the pivotal role that destination marketing organisations can play in facilitating the design and implementation of event portfolio strategies based on the cross-leveraging of areas of relatedness between the events.